Tingkat Kepuasan Pasien Terhadap Pelayanan Kefarmasian Di Instalasi Farmasi Rawat Jalan Rumah Sakit Bhineka Bakti Husada - Humaira Fadhilah; Nurlita Nurlita; Ida Listiana (Edu Masda Journal, 2020)
Pharmacy service in the hospital must be prioritised to patient safety which is based on the paradigm of patient oriented, where pharmacist has a role not only focusing on medicine but also on patients. The good quality of pharmacy service can be seen from patients satisfaction. The objective of this research is to determine patient satisfactions level of outpatient pharmacy installation in Bhineka Bakti Husada Hosiptal. The research used non-experimental research design by descriptive. The number of sampel taken in this research was 100 respondent. The patients satisfactions level was calculated by the result of questionnaires which assessed from 5 dimentions. The satisfactions level analysis was conducted through calculation on the average of performance and expectancy.The research showed that deployment of service given in the installation pharmacy outpatient Bhineka Bakti Husada Hospital with level of conformity satisfaction and expectations > 75% of dimensions 91,6% reliability, 91,5% responsiveness, 92,57% assurance, 89,68% emphaty and 90,27% tangible. The results of this research show that patients are satisfied with the service provided in the installation  pharmacy outpatient Bhineka Bakti Husada Hospital.